Mammary Gland Tropism and Milk-Mediated Transmission of H5N1 in Dairy Cattle: Implications for One Health Surveillance - Kehui Zhang; Yixiang Wang; Xuanrong Wang; Fang Wang; Guanlong Xu; Jie Wang; Zhaofei Wang; Yuqiang Cheng; Heng’an Wang; Yaxian Yan; Jianhe Sun; Jingjiao Ma (Veterinary Sciences, 2026)
Highly pathogenic avian influenza H5N1 virus (H5N1 HPAIV) has long circulated in wild waterfowl and poultry and continues to cross species barriers, posing sustained threats to livestock productivity and public health. The 2024 outbreak of H5N1 HPAIV in dairy cattle across multiple U.S. states represents the first recognized large-scale transmission event of this virus in ruminants, reshaping our understanding of its host range and transmission ecology. This review summarizes recent advances in the epidemiology, virological characteristics, transmission, pathogenesis, surveillance, and control of dairy cattle-associated H5N1. The initial multistate outbreak was dominated by clade 2.3.4.4b genotype B3.13, whereas subsequent independent introductions of genotype D1.1 demonstrated that repeated avian-to-cattle spillover also contributes to the evolving outbreak ecology. A defining feature is efficient replication in bovine mammary epithelial cells, resulting in high viral titers in milk, supporting milk-associated exposure and milking-related contamination as plausible components of transmission, although the relative contribution of different routes remains unresolved. Infected cattle typically show reduced feed intake, a marked decline in milk production, abnormal milk, and mild systemic signs, whereas severe respiratory disease and mortality are uncommon. Mutations such as PB2-M631L, PA-K497R, and changes in NP and NS1 may promote replication and immune evasion in bovine cells, while genotype-specific PB2 adaptations highlight the potential for further mammalian adaptation. Human infections reported to date have been predominantly mild and associated with occupational exposure, with no evidence of sustained human-to-human transmission. Experimental vaccine studies have begun to demonstrate immunogenicity in cattle, although protection against mammary infection, viral shedding, and transmission remains to be established. Future priorities include clarifying mammary tropism and transmission dynamics, while strengthening diagnostics, farm biosecurity, vaccination, evaluating cattle vaccination strategies, and integrated One Health surveillance.